“Pill-in-the-Pocket” Treatment of Propafenone Unmasks ECG Brugada Pattern in an Atrial Fibrillation Patient With a Common SCN5A R1193Q Polymorphism - Li, Linling; Ruan, Yanfei; Liu, Nian; Zhao, Qianqian; Zhang, Mengxia; Li, Xin; Zuo, Song; Le, Jiang; Wu, Kui; Bai, Rong; Ma, Changsheng (Frontiers in Physiology, 2019)
Background: “Pill-in-the-pocket” (PIP) treatment with type IC drugs for cardioversion of recent-onset atrial fibrillation (AF) has been recommended in guidelines. Major adverse effects have been often reported, the underlying mechanisms are proposed to be associated with the genetic backgrounds. Methods and Results: A male patient was treated with PIP approach (propafenone 600mg.po) for the conversion of new onset AF. His symptoms got worse and referred to emergency room; ECG showed a typical Brugada syndrome (BrS) type I ECG pattern with sinus rhythm. Genetic screening identified a common SCN5A polymorphism R1193Q. Propafenone blockade of INa was studied in HEK293 cells expressed SCN5A R1193Q channel and WT channel using patch clamp techniques. There was no significant difference in peak current and steady-state gating parameters between R1193Q and WT at baseline. At clinically relevant concentration of 2 μmol/L propafenone, use-dependent block (UDB) of INa was more pronounced in R1193Q versus WT (44.2±7.2% versus 24.8±5.7% at the frequency of 2 Hz, P<0.05); IC50 of UDB was 2.9±0.7 µmol/L for R1193Q and 8.1±1.8 µmol/L for WT respectively. Propafenone produced more left shift of steady-state inactivation and slower recovery from inactivation in R1193Q compared with WT. Conclusion: A common SCN5A polymorphism R1193Q enhances UDB by propafenone and predisposes the patients to drug-induced BrS with PIP treatment. Our data suggest that R1193Q polymorphism is likely to be a genetic marker for the major adverse effects associated with PIP approach for AF patient management.